Building a Dream: Learning Communities in the Basque Country - Mª Luisa Jaussi; Carmen Vega (Networks: An Online Journal for Teacher Research, 2004)
All of us that make up the Learning Communities project share the same dream, the same utopia: that all children regardless of their social situation, their culture, their personal characteristicsare able to develop, to a maximum, their abilities and enjoy the same rights and real opportunities in today's society. It is a dream of equality that includes difference. We think that "another education is possible" and for this, it is necessary that more people join this utopia, as is already happening in the Basque Country, where increasingly more schools are starting the transformation process. The dream is one of the phases in the process of transforming a center into a Learning Community. It is the catalyst for enthusiasm, meaning and enchantment.